Stream Segregation in Household Use: A Review of Grey Water as an Alternative Source of Water and Yellow Water as an Alternative Source of Fertilizers - Beler-Baykal, B. (Springer Science and Business Media LLC, 2014)
Resource recovery and conservation of resources have been attracting increasing attention in the recent years for finding sustainable solutions to environmental problems. One of such efforts is segregation of domestic wastewater streams as grey, yellow and brown or black water. This enables revaluation of domestic wastewater as an alternative renewable source of water as well as a potential source of plant nutrients, i.e. fertilizers. Reuse of grey water (the stream excluding toilet wastewater) can help reduce the unnecessary utilization of pristine water in line with “fit for purpose” use and can provide an alternative source for water stressed/scarce areas. Yellow water (human urine) constitutes only 1 % of conventional domestic wastewater by volume yet contains over 80 % of nitrogen, over 50 % each of phosphorus and potassium, hence lending a high potential to be used as fertilizer. Direct and indirect application may be practiced. Ion exchange/adsorption with clinoptilolite is a promising option for indirect use. Recoveries exceeding 90 % have been attained for nitrogen and phosphorus from clinoptilolite exhausted with NP and the use of plant nutrients in yellow water as an alternative source of fertilizers. Segregated collection provides a promising route towards sustainability by contributing to “fit for purpose” use of scarce fresh water resources through the reuse of grey water while providing a means of conservation through the recovery of plant nutrients from “wastes”.